ANALISIS INTERVENSI GIZI SPESIFIK TERHADAP KEJADIAN STUNTING PADA BALITA DI PUSKESMAS KILANG KOTA AMBON - Bellytra Talarima; Ivy Violan Lawalata (LLDIKTI Wilayah X, 2023)
Stunting occurs in almost all regions of Indonesia, one in three under five and toddlers is stunted, the prevalence of stunting based on the 2022 Indonesian Nutrition Status Study (SSGI) is 21.6%. Data on stunting toddlers in the working area of the Ambon City Refinery Health Center in 2021 totals 50 toddlers. The purpose of this study was to determine the relationship and magnitude of the risk of exclusive breastfeeding, initiation of early breastfeeding, the appropriateness of giving MP-ASI and a history of childhood infectious diseases with the incidence of stunting. The research method used was analytic observational with a cross-sectional approach. The study was conducted at the Ambon City Refinery Health Center, the number of samples was 115 under-fives with a purposive sampling technique, the data were analyzed using the chi-square test with a value of α = 0.05. The results showed that there was a relationship between exclusive breastfeeding with a p value = 0.03 and a prevalence ratio (PR) CI of 95% = 1.722; Early initiation of breastfeeding with a p value = 0.02 and a prevalence ratio (PR) CI of 95% = 2.314; The accuracy of complementary feeding with a p value = 0.00 and a prevalence ratio (PR) CI of 95% = 1.927; and a history of infectious diseases under five with a p value = 0.02 and a prevalence ratio (PR) CI of 95% = 2.643. It is hoped that the participation of all parties in efforts to prevent, control and overcome stunting. Keywords: specific nutrition; Exclusive breastfeeding; MP-ASI; IMD; stunting